What is the ‘Future’ of Greek? Towards a Pragmatic Analysis - Chiou, Michael (Research in Language, 2014)
The paper investigates the problems related to futurity and modality in modern Greek. The discussion of Greek temporal future expressions is conducted with reference to relevant literature from the areas of English linguistics, cognitive studies and pragmatics. The focus is on the status of future-oriented expressions and the question whether they are primarily epistemic in nature, whether they are tense-based, or modality-based. It is argued that the future tense in Greek has a modal semantic base conveying epistemic modality and that the preferred future prospective reading is a pragmatic development of the semantic modal base. The author further suggests that the future reading is a kind of presumptive meaning which follows from the neo-Gricean Principle of Informativeness, known as the I-principle (Levinson 2000) being a generalised interpretation which does not depend on contextual information.